Market Efficiency in Palm Oil and Cocoa Futures - Kaur, Bisant (1994)

(untitled)
Futures markets play an important role in the price discovery and forward pricing of agricultural commodities. Agricultural product prices have been found to be particularly volatile and susceptible to sharp fluctuations which expose producers and traders to increased risks in handling these products. For countries like Malaysia which depend on commodity earnings for a substantial portion of their inflow of foreign exchange, severe fluctuations in prices could have unfavourable effects on the economy. The effects of futures prices on cash prices have been the subject of much research in recent years. The contention is that if the futures market is efficient, then futures prices should provide unbiased forecasts of cash prices in order to facilitate optimal production and storage decisions. Many empirical studies have in fact shown that futures trading leads to more efficient spot markets. The development of futures markets in Malaysia was to fulfill the need for an efficient pricing and hedging mechanism for Malaysia's primary commodities. Whether that objective has been fulfilled after twelve years since the setting up of the Kuala Lumpur Commodity Exchange (KLCE) is the subject of this study. Over the years, the commodity base of the exchange has expanded from crude palm oil (CPO) to rubber, tin, cocoa and refined, bleached and deodorized (rbd) palm olein. The pricing efficiency of the CPO futures market is evaluated in this study since it has important inferences for the later established futures markets. The hypothesis tested is whether the futures market is informationally efficient. Comparisons are made with cocoa futures which were introduced only recently on the exchange and which represents another commodity where Malaysia has had to depend on world markets {or domestic price determination. This study evaluates pricing efficiency by using the cointegration approach which examines the nature of the relationship between cash and futures prices for a commodity. This method overcomes the problems associated with previous methods on testing futures market efficiency. Assessments on the efficiency of the market are based on the degree of divergence and the speed of adjustment between cash and futures prices. Daily prices over the period 1981 to 1992 were used for CPO and a two year period between 1989 and 1990 were covered for cocoa.The results obtained indicate that in the case of the CPO market, with only one exception, there was generally cointegration between cash and futures prices for the period studied, implying pricing efficiency in the market. It was also found that a mechanism existed which brought cash and futures prices into alignment whenever they diverged. The evidence also points to the dependence of cash markets on future markets for price indications. The only exception was in 1984, and this was the year in which the KLCE was embroiled in a crisis. The structural defects of the market appears to have affected the pricing performance to such an extent that futures and cash prices went out of alignment. In the case of the cocoa market, the results indicate that futures and cash prices were cointegrated and there was pricing efficiency. But the subsequent decline of trading interest in the market indicates that there were structural defects which had led to a loss of confidence in the market and affected liquidity. This study therefore underlines the possible influence of market structure on the pricing performance of the market.